Adopsi International Financial Reporting Standards (IFRS) di Negara-negara Muslim: Perspektif Institutional Theory - Elsa Nuriyani; Sepky Mardian (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2019)
The aim of this study is to discover the adoption of International Financial ReportingStandards convergence enforced in Muslim countries. The population of this study is27 Muslim states in the world, while the sample of this study are 7 Muslim States, i.e.;Saudi Arabia, Malaysia, Bangladesh, Egypt, Nigeria, United Arab Emirates, andIndonesia. The results of this study indicate that most of the Muslim countries in theworld have converged their accounting standards with IFRS for certain reasons thatarised from each country. Although there are some countries that do not carry out theconvergence throughly due to standard nonconformities with existing policies in thosecountries.